A Survey of Bacterial Microcompartment Distribution in the Human Microbiome - Asija, Kunica; Sutter, Markus; Kerfeld, Cheryl A. (Frontiers in Microbiology, 2021)
Bacterial microcompartments (BMCs) are protein-based organelles that expand the metabolic potential of many bacteria by sequestering segments of enzymatic pathways in a selectively permeable protein shell. Sixty-eight different types/subtypes of BMCs have been bioinformatically identified based on the encapsulated enzymes and shell proteins encoded in genomic loci. BMCs are found across bacterial phyla, and the organisms that contain them, rather than strictly correlating with specific lineages, tend to reflect the metabolic landscape of the environmental niches they occupy. From our recent comprehensive bioinformatic survey of BMCs found in genome sequence data, we find many in members of the human microbiome. Here we survey the distribution of BMCs in the different biotopes of the human body. Given their amenability to be horizontally transferred and bioengineered they hold promise as metabolic modules that could be used to probiotically alter microbiomes or treat dysbiosis.